EVALUATION OF THE ENGINEERING PROPERTIES OF CASHEW KERNEL OBTAINED FROM DIFFERENT PLANTATIONS IN NSUKKA (Nigerian Journal of Technology, 2019)
In this study, the engineering properties of cashew kernels grown in Nsukka were evaluated. The experiments were carried out in replicates from different plantations in order to achieve near accurate average values. The results showed no significant difference in the physical and thermal properties while terminal velocity, coefficient of friction, compressive force and stress were significantly different. Thus, since the physical properties were significantly the same then a processing system developed using the property values of a particular batch of kernel can be conveniently used with any other batch of the kernel. However varying force applications are to be used depending on the batch due to significant differences in the values of the mechanical properties and end-product of operation the same due to the fact that deformation was significantly the same. The thermal response of any batch will be the same since the thermal properties were significantly the same.  http://dx.doi.org/10.4314/njt.v38i2.31